Prevalent and diverse new plasmid-encoded heavy metal and antimicrobial resistance in Klebsiella strains isolated from hospital wastewater - Engobo, Grace Pascale; Su, Wenya; Wang, Shengyao; Yan, Zhen; Zhang, Youming; Zhang, Mengge; Geng, Xueyun; Xu, Hai; Li, Ling; Wang, Mingyu (Frontiers in Cellular and Infection Microbiology, 2025)
The rise of antibiotic-resistant Klebsiella pneumoniae poses a significant global health threat. Plasmids, as mobile genetic elements, play a critical role in bacterial adaptation by facilitating the spread of resistance genes. To analyze plasmid-mediated antibiotic and heavy metal resistance in clinical Klebsiella strains, 33 Klebsiella strains isolated from wastewater were subjected to third-generation nanopore sequencing to obtain high-quality whole-genome assemblies. The presence and diversity of plasmids associated with antibiotic and heavy metal resistance were analyzed, and phenotypic assays were conducted to confirm metal resistance. A total of 81 plasmids were identified across 24 strains, including 28 (34.6%) novel plasmids. Among them, 22 plasmids carried antibiotic resistance genes (ARGs), with 12 containing integrons, four of which were complex Class I integrons and two unconventional integrons. Notably, a novel conjugative plasmid, pKP228-1, was discovered carrying a complex Class I integron with a unique gene cassette array encoding 12 ARGs, and harboring blaNDM-1 in the adjacent ISCR1-associated region. Another plasmid, pKP174-2, harbored mcr-8.1 and tporJ1-tmexCD1. Additionally, 24 plasmids encoded resistance to eight heavy metals/metalloids, and 12 plasmids co-harbored both ARGs and metal resistance genes, indicating potential co-selection mechanisms. This study highlights the extensive diversity and novel structures of plasmids carrying both antibiotic and heavy metal resistance in clinical Klebsiella isolates. The observed co-occurrence of the two resistance types highlights the need for comprehensive genomic surveillance to monitor the spread of multi-resistance determinants.